TIPS DAN TRIK PEMBAHASAN SOAL UN BAHASA INDONESIA BAGI SISWA KELAS IX SMP NEGERI 4 KOTA SOLOK - Mega Putri; Elan Halid; Zona Rida Rahayu (PUAN INDONESIA, 2022)
In education, one of the evidences of success in the learning process is with the achievement of the test results obtained. The national exam is evaluation system of national primary and secondary education standards and quality equality inter-regional education level conducted by the Center for Educational Assessment, Ministry of National Education in Indonesia based on the Law of the Republic of Indonesia No. 20 of 2003 states that in the context of controlling the quality of education nationally, an evaluation is carried out as a form of accountability of education providers to parties who interested. Indonesian subjects are important for all students because position as the national language. Indonesian subjects have been studied starting from elementary school students up to the college level. However, this subject is still a scourge which is scary because in the evaluation it is considered that there are many trapping questions. other than that The text-based 2013 curriculum requires students to be able to understand the text before they answer the exam questions. students also have difficulty reading quickly thus spending a lot of time to solve the problem of the form of the text in exams, especially for middle school students. Guidance is needed for students in answering UN questions in order to get satisfactory results.The activities carried out in this service are making try out questions National Examination, then the implementation of the National Examination pretest, and discussion of questions the. In the discussion students are given guidance in answering exam questions National which has been prepared in advance. The implementation of the pretest the average score of students is 65 while after the guidance was carried out in the form of discussion of the UN questions so that the average score of students increased. There appears to be a significant change in student scores. They are also very enthusiastic in discussing the existing problems. They are also fighting for answer the questions discussed together.